Explaining Psychological Capital Components through Organization’s Ethical Climate Components - Golparvar, Mohsen; Azarmonabadi, Afsaneh Rahmati (International Journal of Business, Economics and Management, 2014)
Organization’s ethical climate and its components are among major factors affecting employee’s different behaviors and emotions in work environments. Accordingly, the role of organization’s ethical climate components (caring, laws, rules, services and independence) on psychological capital components (self-efficacy, hope, resiliency and life orientation) was studied in this research. For this purpose, 267 employees of railway company, Isfahan, Iran, were selected and answered organization’s ethical climate and psychological capital questionnaires in a correlation research. The hypotheses of this research were analyzed by Pearson correlation coefficient and multiple regression analysis. The results showed that there is a significant positive relationship between some of the organization’s ethical climate components and self-efficacy, hope, resiliency and life orientation. Results of the regression analysis indicated that service and independence can predict the self-efficacy and hope; laws and rules, and service can predict resiliency and caring, and service can predict life orientation.